2019
DOI: 10.1038/s41598-019-45660-8
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary examination of bacterial, archaeal, and fungal communities inhabiting different rhizocompartments of tomato plants under real-world environments

Abstract: Plant microbiota is a key determinant of plant health and productivity. The composition and structure of plant microbiota varies according to plant tissue and compartment, which are specific habitats for microbial colonization. To investigate the structural composition of the microbiome associated with tomato roots under natural systems, we characterized the bacterial, archaeal, and fungal communities of three belowground compartments (rhizosphere, endosphere, and bulk soil) of tomato plants collected from 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
69
1
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 82 publications
(97 reference statements)
13
69
1
4
Order By: Relevance
“…It is widely accepted core microbial communities presented in the gut microbiomes of humans and other animals, as well as root microbiomes of plants [4,5,7,8,19,20]. Assembly of rhizosphere microbiome in plant is driven by many aspects, including climate environment, soil source, host developmental stage, cultivation practice, and root architecture [5][6][7][8]11,14,[21][22][23][24]. Biotic factors, such as plant genotypes, pathogens, biocontrol microorganisms, and seed bacteria also alter and influence the microbial communities in rhizosphere environment [5][6][7][8][12][13][14][26][27][28][29][30][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is widely accepted core microbial communities presented in the gut microbiomes of humans and other animals, as well as root microbiomes of plants [4,5,7,8,19,20]. Assembly of rhizosphere microbiome in plant is driven by many aspects, including climate environment, soil source, host developmental stage, cultivation practice, and root architecture [5][6][7][8]11,14,[21][22][23][24]. Biotic factors, such as plant genotypes, pathogens, biocontrol microorganisms, and seed bacteria also alter and influence the microbial communities in rhizosphere environment [5][6][7][8][12][13][14][26][27][28][29][30][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The rhizosphere microbiota of the plant is mainly dominated by the bacterial phyla Proteobacteria, Bacteroidetes, and Acidobacteria [2,5,19,20]. In tomato, some studies on the community composition of the rhizosphere microbiota have reached the same conclusion using both culture-dependent and culture-independent approaches [15,[22][23][24][25][26]. Qiao et al [26] found that the three most abundant core phyla in the tomato (Solanum lycopersicum cv.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An experimental design where bulk soil, rhizosphere soil and plant roots are sampled and microbial communities determined for each of the three compartments can easily produce a contingency matrix [10, 11]. Based on the matrix, beta-diversity are usually calculated, showing the compositional similarity of microbial community between each other.…”
Section: Figmentioning
confidence: 99%